2020
DOI: 10.1080/08941939.2020.1830318
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical and Histological Characteristics of Phasix™ ST Mesh in a Porcine Model of Hernia Repair

Abstract: Purpose: The objective of this study was to determine mechanical and histological properties of Phasix TM ST Mesh in various defect sizes and characterize the tissue replacing Phasix TM ST Mesh in a porcine model of ventral hernia repair. Methods: Simulated hernia defects were surgically created in the midline of twenty-four (n ¼ 24) Yucatan pigs. Treatment groups included 8 cm defect sutured closed (buttress) and unclosed 4 cm and 8 cm defect groups. Phasix TM ST Mesh (15 cm diameter circle) was implanted lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Fourteen publications identified by this scoping review involved preclinical studies in a variety of animal models and species, including pigs, rats, rabbits, sheep, mice, and vervets (Figure 2, and Table 1) (6,23,24,26,36,37,(43)(44)(45)(46)(47)(48)(49)89). Three of these studies (n = 3) contained both a benchtop component and a preclinical component (6,36,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen publications identified by this scoping review involved preclinical studies in a variety of animal models and species, including pigs, rats, rabbits, sheep, mice, and vervets (Figure 2, and Table 1) (6,23,24,26,36,37,(43)(44)(45)(46)(47)(48)(49)89). Three of these studies (n = 3) contained both a benchtop component and a preclinical component (6,36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies demonstrate long-term resorption of P4HB over a period of approximately 12–18 months, during which the mesh loses all of its mechanical strength ( 6 , 43 , 44 , 47 ). The clinical studies identified in this literature review provided insight into the performance of P4HB in a variety of patient populations and clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the authors compare the longer term results of using a P4HB mesh with an anti-adhesive visceral protective layer during laparoscopic repair in a pig model. 6 Different types of hernia defects were created, 8 cm diameter with defect closure, and both 4 and 8 cm hernias without defect closure; all were treated with a circular 15 cm diameter P4HB-ST mesh. A little bit surprisingly, all repaired hernia sites exhibited similar mechanical strength as well as histological properties, independent of both hernia size, defect closure, and follow-up time (48 and 72 weeks after implantation).…”
Section: Frederik Berrevoetmentioning
confidence: 99%
“…Currently there are over one hundred mesh variations on the market [ 2 ], including conventional synthetic meshes as well as newer biological products. More recently, industry has continued this innovation by developing new absorbable “biosynthetic” meshes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%